Optimal Design of Mises Truss with Respect to Time to Creep Rapture - K. Szuwalski (Engineering Transactions, 1994)
The paper deals with problem of optimal choice of slope angle for bars of Mises truss in creep conditions. Results of optimization with respect to brittle creep rupture coincide with elastic solution (45°), while for ductile creep rupture there is no optimum – the longest life – time is obtained for initially horizontal bars. Introduction of limitation for admissible strains makes it possible to find continuous transition from brittle to ductile rupture. The same possibility gives application of Kachonov's mixed rupture theory.